PUNICA GRANATUM MENAIKKAN KADAR GLUTATHION PEROXYDASE PADA KULTUR HUVECs YANG DIPAPAR PLASMA PRE EKLAMPSI - Januarsih, Januarsih; Fitria Jannatul Laili; Megawati, Megawati (Jurnal Cakrawala Ilmiah, 2024)
Preeclampsia and Eclampsia rank as the number one cause of maternal death in Indonesia Preeclampsia is a syndrome associated with symptoms of vasospasm, increased peripheral vascular resistance and decreased organ perfusion. One of the current etiological theories of preeclampsia is that there is an imbalance between the production of free radicals and the antioxidant defense system that causes oxidative stress, characterized by a decrease in antioxidant activity accompanied by an increase in lipid peroxide levels (oxidants / free radicals). Oxidative stress can be controlled by administering anti-oxidants which are divided into enzymatic and non-enzymatic antioxidants. Enzymatic antioxidants consist of Superoxyd Dismutase (SOD), Glutathione peroxydase (GPx) and Catalase (Cat). Red pomegranate (Punica granatum) contains phytochemicals and is rich in compounds that function as antioxidants, namely polyphenols, tannins and anthocyanins. The purpose of this study was to determine the effect of red pomegranate (Punica granatum) extract on GPx levels in HUVECs cultures exposed to preeclamptic plasma. The research design was a complete randomized experimental design with 5 treatment groups. Red pomegranate extract is able to increase GPx levels because red pomegranate is rich in antioxidants. Red pomegranate (about 50% of the total weight of pomegranate) consists of 80% juice and 20% seeds. The juice itself contains 85% water, 10% sugar and 1.5% pectin, ascorbic acid and flavonoid polyphenols.